Developing new radiotherapy techniques using linac based gamma radiation sources - Arruda-Neto, J. D T; Bittencourt-Oliveira, M. C.; Schenberg, A. C G; Silva, E. C.; Mesa, J.; Rodrigues, T. E.; Garcia, F.; Louvison, M.; Paula, C. R. (My University, 2007)
A major challenge in cancer radiotherapy is to deliver a lethal dose of radiation to the target volume while minimizing damage to the surrounding normal tissue. We have proposed a model on how treatment efficacy might be improved by interfering with biological responses to DNA damage using exogenous electric fields as a strategy to drastically reduce radiation doses in cancer therapy. This approach is demonstrated at this Laboratory through case studies with prokaryotes (bacteria) and eukaryotes (yeast) cells, in which cellkilling rates induced by both gamma radiation and exogenous electric fields were measured. It was found that when cells exposed to gamma radiation are immediately submitted to a weak electric field, cell death increases more than an order of magnitude compared to the effect of radiation alone. This finding suggests, although does not prove, that DNA damage sites are reached and recognized by means of long-range electric DNA-protein interaction, and that exogenous electric fields could destructively interfere with this process. As a consequence, DNA repair is avoided leading to massive cell death. Here we are proposing the use this new technique for the design and construction of novel radiotherapy facilities associated with linac generated gamma beams under controlled conditions of dose and beam intensity.
Keywords: Cell death; DNA; Dosimetry; Electric field effects; Electric field measurement; Electric fields; Gamma rays; Genes; Linear accelerators; Nucleic acids; Organic acids; Quantum optics; Radiotherapy; Theorem proving; Beam intensities; Biological responses; Cancer therapies; Case studies; Controlled conditions; Design and constructions; Dna damages; Dna repairs; Gamma radiation sources; Gamma radiations; Lethal doses; New techniques; Normal tissues; Protein interactions; Radiation doses; Target volumes; Radiation